The Role of China’s ICT Investments and Strategic Communication in Enhancing Influence in Kenya - Maina, Charity; Fitriani, Evi (Universitas Medan Area, 2025)
China's economic engagement with Africa has evolved to include extensive investments in ICT as part of its Digital Silk Road initiative. In Kenya, Chinese ICT investments began in 1998 to establish a national telecommunications ecosystem. Drawing on Network Power and Communication Power, this study examines the role of DSR and communication strategy in shaping Kenya's digital and communication landscape. This paper argues that China's investments in Kenya have introduced digital standards, media communication platforms, and infrastructure, creating asymmetrical relations and controlling public narratives. By leveraging its investments, China built Kenya's telecommunications backbone, embedding its technological standards and limiting Kenya's ability to switch to alternative ICT providers and products. Consequently, Chinese ICT products dominate Kenya's market. Furthermore, the presence of Chinese state media in Kenya has shaped information flows and media content, blurring the line between economic development and strategic communication. This study contributes to understanding the strategic use of Chinese ICT investments to extend influence in Kenya, a regional leader in East Africa, through technological integration and communication networks.